Analysis of the Influence of Fear of Missing Out (FOMO) and Hedonism Lifestyle on Online Purchase Decisions Based on Impulsive Buying Behavior on Fast Fashion Products in Tiktok Social Media - Irfa Ma’rifah; Ratna Kusumawati (Universal Business and Management Review, 2025)
This study aims to examine the influence of Fear of Missing Out (FOMO) and a Hedonistic Lifestyle on online purchasing decisions for fast-fashion products, both directly and indirectly through Impulsive Buying as an intervening variable on TikTok. This study employed a quantitative approach with descriptive analysis. The sampling technique used was purposive sampling. The survey was conducted among 76 students from the 2021 intake of the Faculty of Economics and Business at Wahid Hasyim University, Semarang. Data were analyzed using Path Analysis, Mediation (Sobel Test), and Partial t-Test using IBM SPSS (Statistical Package for the Social Sciences) Version 16. The results showed that: (1) Fear of Missing Out (FOMO) had a negative and significant effect on online purchasing decisions; (2) Hedonistic Lifestyle had a positive and significant effect on online purchasing decisions; (3) Fear of Missing Out (FOMO) had a positive and significant effect on online purchasing decisions through Impulsive Buying. (4) Hedonistic Lifestyle has a negative and significant influence on Online Purchasing Decisions through Impulsive Buying.